Ludovico Silva: ideología y educación (2020)
The purpose of this research is to analyze in the work of Ludovico Silva his contributions on the theme of ideology and its link to education, from a hermeneutical perspective that seeks to interpret circumstantially the reflections of this Venezuelan socialist intellectual of the late twentieth century. A criticism of all ideology is revealed in his texts for becoming a justification of social relations that dehumanize, for which he promotes the cultivation of critical consciousness through education away from dogmas.